The Baltic Countries : From Economic Stabilization to EU Accession - Le Gall, Francoise (Occasional Papers; Occasional Paper ;, 1998)
Are the three Baltic countries, Latvia, Estonia, and Lithuania, ready for accession to the European Union? Have their economies overcome the problems of transition? The answers to these questions and their implications for policy are provided in this collection of analyses. Rather than a country-by-country description, the volume provides a cross-country perspective of developments from 1994 through mid-1997. The seven sections of this paper discuss recent macroeconomic and structural policies, exchange rate regimes, fiscal issues, financial systems, private sector development, and accession to the European Union.